CAA2016: Oceans of Data : Proceedings of the 44th Conference on Computer Applications and Quantitative Methods in Archaeology - Mieko Matsumoto; Espen Uleberg (Archaeopress Archaeology, 2018)
CAA2016: Oceans of Data gives an up-to-date overview of the field of archaeology and informatics. It presents ground-breaking technologies and best practice from various archaeological and computer science disciplines. The articles in this volume are based on the foremost presentations from the 44th Computer Applications in Archaeology Conference 2016, held in Oslo. The theme of CAA2016 was ‘Exploring Oceans of Data', alluding to one of the greatest challenges in this field: the use and reuse of large datasets that result both from digitalisation and digital documentation of excavations and surveys. The volume contains 50 peer-reviewed and highest-ranked papers that are divided in eight parts, including an introduction and seven chapters. The introduction sets the stage with Oceans of Data (C.-E. Ore) and Theorising the Digital (S. Perry and J. S.Taylor), discussing the current status of overall CAA research. These two papers present the current developments, challenges, and potential that lies ahead from different perspectives. Ore points to the importance of common authority systems and ontologies. Common conceptual data models will ease curation and secure long-term reusability. Perry and Taylor address the need to bring together theoretical and digital archaeology. In the following chapters, different topics are presented under the headings Ontologies and Standards, Field and Laboratory Data Recording and Analysis, Archaeological Information Systems, GIS and Spatial Analysis, 3D and Visualisation, Complex Systems Simulation, and Teaching Archaeology in the Digital Age.